Digital Literation Based Learning Strategy in Improving Student Learning Participation in Education in Pandemi Era - Mundir, Mundir (International Journal of Supply Chain Management, 2020)
Abstract This phenomenological qualitative research aims to analyze and describe the steps of internet-based learning, the underlying learning model, and the experience of lecturers and students while carrying out internet-based learning in the context of strengthening digital literacy. The results showed that internet-based learning in a pandemic situation to strengthen digital literacy must be started by preparing an internet connection, attendance list (online and manual), shared RPS via WhatsApp, pretest / quiz, learning offline / online, then presentation. review the material, posttest / quiz and end with motivation. The learning model used is active learning, a model that can provide special experience for lecturers and students. They always prepare attendance lists and material online, are disciplined, and are accustomed to using the internet. But they still encounter technical obstacles related to the use of digital media and the internet, as well as electricity and digital media disruptions that were difficult to predict beforehand.